Framing the mother: childhood obesity, maternal responsibility and care - Maher, J.; Fraser, Suzanne; Wright, J. (Routledge, 2010)
Currently in developed nations, childhood obesity is generating widespread concern and prompting social and institutional responses. Obesity is constructed as a broad public health crisis, but individuals are constructed as responsible for their own bodies and body sizes within this crisis. We are particularly interested in two aspects that focus on women as central to this phenomenon; the first is the imputation of maternal responsibility for the weight of children and the second is the role that specific fears about flesh and women's bodies play in how childhood obesity is represented. We analyse media representations of childhood obesity in Australia and draw out the discourses of maternal responsibility and the intertwining of mothers and children's bodies. We frame the childhood obesity crisis within a broader discussion of women, care and responsibility, suggesting that childhood obesity offers another embodied location to reinforce and extend women's roles and responsibilities as mothers, in response to changing patterns of work and care.